1996
DOI: 10.1152/ajpregu.1996.270.5.r1005
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of transcription factor C/EBP-beta in stimulation of PEPCK gene expression during exercise

Abstract: Prolonged exercise increases gluconeogenesis and activates transcription of the hepatic phosphoenol pyruvate carboxykinase (PEPCK) gene. The mechanisms that regulate the transcriptional control of gene expression depend on the interaction of nuclear proteins with distinct DNA sequences. To determine the involvement with the liver-enriched transcription factor CCAAT/enhancer binding protein beta (C/EMP-beta) in the induction of PEPCK gene transcription during prolonged exercise or adenosine 3',5'-cyclic monopho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 0 publications
2
32
1
Order By: Relevance
“…The following year, in accordance with previous work published by this lab, Angrand et al (49) found that a full glucocorticoid response for PEPCK requires the CRE. Soon afterward, in a set of in vivo studies using transgenic mice, Friedman and colleagues (50,51) correlated the dramatic increase in C/EBP␤ levels with the CRE-dependent glucocorticoid induction of PEPCK gene transcription during exercise.…”
Section: Discussionmentioning
confidence: 99%
“…The following year, in accordance with previous work published by this lab, Angrand et al (49) found that a full glucocorticoid response for PEPCK requires the CRE. Soon afterward, in a set of in vivo studies using transgenic mice, Friedman and colleagues (50,51) correlated the dramatic increase in C/EBP␤ levels with the CRE-dependent glucocorticoid induction of PEPCK gene transcription during exercise.…”
Section: Discussionmentioning
confidence: 99%
“…Other data indicate that the binding of C/EBP␤ to the PEPCK promoter may be increased by cAMP. When animals are injected with cAMP, the abundance of C/EBP␤ rises rapidly in the liver and the binding of C/EBP␤ to the P3(I) site increases (37). In physiologic situations such as with increased exercise, the abundance of C/EBP␤ increases in the liver (37).…”
Section: Reporter Vectormentioning
confidence: 99%
“…When animals are injected with cAMP, the abundance of C/EBP␤ rises rapidly in the liver and the binding of C/EBP␤ to the P3(I) site increases (37). In physiologic situations such as with increased exercise, the abundance of C/EBP␤ increases in the liver (37). Our data 3 responsiveness to a PEPCK promoter HepG2 cells were transfected with 5 g of Ϫ490-PCAT, 5 g of RSV-TR␤, 5 g of Gal4-C/EBP␣ fusion plasmid, and 5 g of SV40-␤-gal as described in Table I demonstrate that, when C/EBP␤ is bound to the P3(I) site, it can stimulate basal expression and contribute to cAMP responsiveness.…”
Section: Reporter Vectormentioning
confidence: 99%
“…The metabolic adaptation to exercise is not restricted to the working muscle. It has been recognised for decades that the liver, as a major regulator of glucose and lipid homoeostasis, also responds to acute exercise, and increased activities of the gluconeogenic enzymes as well as decreased lipogenic enzyme activities have been found [18][19][20]. Compared with the numerous reports on the transcriptional regulation of genes in the working muscle, remarkably little data on exercise-induced gene expression in the liver are available.…”
Section: Introductionmentioning
confidence: 99%